Science and the Life-World : Essays on Husserl's Crisis of European Sciences. - Hyder, David Jalal, 1964- (Stanford University Press, 2010)
This collection of essays by prominent philosophers treats Husserl's last work, The Crisis of European Sciences, which deals with the relation of science to the world of everyday experience.